Inductive logic programming : 29th International Conference, ILP 2019, Plovdiv, Bulgaria, September 3-5, 2019, Proceedings /: 29th International Conference, ILP 2019, Plovdiv, Bulgaria, September 3-5, 2019, Proceedings. (2020) - Unknown
No abstract available